Analisis Kesulitan Membaca Permulaan Siswa Kelas II SD Negeri 14 Kelakik - Tuti Elviyanti; Mastiah; M Akip (JURNAL PENDIDIKAN DAN PEMBELAJARAN SEKOLAH DASAR, 2026)
Abstract This study aimed to analyze the beginning reading difficulties of second-grade students at SD Negeri 14 Kelakik using the Early Grade Reading Assessment (EGRA) instrument. The study employed a descriptive qualitative method with data collection techniques consisting of observation, interviews, documentation, and reading tests. The subjects were 23 second-grade students, of whom 8 students experienced beginning reading difficulties. The findings showed that students experienced difficulties in recognizing letters, reading meaningful words, reading non-meaningful words, reading fluently and comprehending texts, as well as listening comprehension. The most dominant difficulty was reading non-meaningful words with an average score of 10%. Students also had difficulty distinguishing similar letters such as “b” and “d” or “f” and “v”, reading fluently, combining letters into words, and understanding reading content. The study concludes that beginning reading skills need continuous practice and guidance to improve students’ reading abilities optimally. Keywords: Beginning Reading Difficulties, Elementary School Students, EGRA, Reading Comprehension. Abstrak Penelitian ini bertujuan untuk menganalisis kesulitan membaca permulaan siswa kelas II SD Negeri 14 Kelakik menggunakan instrumen Early Grade Reading Assessment (EGRA). Penelitian ini menggunakan metode kualitatif deskriptif dengan teknik pengumpulan data berupa observasi, wawancara, dokumentasi, dan tes membaca. Subjek penelitian berjumlah 23 siswa kelas II, dengan 8 siswa mengalami kesulitan membaca permulaan. Hasil penelitian menunjukkan bahwa siswa mengalami kesulitan pada aspek mengenal huruf, membaca kata bermakna, membaca kata tidak bermakna, kelancaran membaca nyaring dan pemahaman bacaan, serta menyimak. Kesulitan yang paling dominan terdapat pada aspek membaca kata tidak bermakna dengan rata-rata skor 10%. Siswa juga mengalami kesulitan membedakan huruf yang bentuknya hampir sama seperti “b” dan “d” atau “f” dan “v”, membaca dengan lancar, merangkai huruf menjadi kata, serta memahami isi bacaan. Penelitian ini menyimpulkan bahwa kemampuan membaca permulaan perlu ditingkatkan melalui latihan dan pendampingan secara berkelanjutan agar kemampuan membaca siswa berkembang secara optimal. Kata kunci: Kesulitan Membaca Permulaan, Siswa Sekolah Dasar, EGRA.